Pengembangan Model Formasi Latihan Bertahan dalam Permainan Bola Voli Indoor - Muhammad Suhairi; Lidwina Via; Ade Rahmat (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to develop a defensive formation training model in indoor volleyball to enhance players’ defensive skills, reaction speed, anticipation, & movement coordination during gameplay. The method study employed a Research & Development (R&D) approach adapted from the Borg & Gall model, consisting of the following stages: needs analysis, product design, design validation, small- & large-group field testing, small-group revision, large-group revision, & final product development. The participants were 15-year-old volleyball athletes involved in a small-group trial of 16 participants & a large-group trial of 40 participants. Data were collected through interviews, observations, questionnaires, & expert validation sheets involving academic experts, practitioners, & motor development specialists. The validation results showed that the developed model obtained a feasibility score of 88% from academic experts, 92% from practitioner experts, & 96% from motor development experts, all categorized as “very feasible.” The small-group trial involving 16 participants achieved an average percentage of 91.75%, while the large-group trial involving 40 participants achieved 93.2%, both categorized as “very feasible.” The developed training model consists of six defensive formation patterns designed to improve defensive positioning, anticipation, communication, & team coordination in volleyball matches. The findings of the study indicate that the developed defensive formation training model is effective, practical, & feasible for use in volleyball training & physical education learning. The model provides innovative & engaging variations of defensive drills that can enhance player involvement & improve defensive performance in indoor volleyball games. Keywords: Defensive Training, Indoor Volleyball, Model Development. This study aimed to develop a defensive formation training model in indoor volleyball to enhance players’ defensive skills, reaction speed, anticipation, & movement coordination during gameplay. The method study employed a Research & Development (R&D) approach adapted from the Borg & Gall model, consisting of the following stages: needs analysis, product design, design validation, small- & large-group field testing, small-group revision, large-group revision, & final product development. The participants were 15-year-old volleyball athletes involved in a small-group trial of 16 participants & a large-group trial of 40 participants. Data were collected through interviews, observations, questionnaires, & expert validation sheets involving academic experts, practitioners, & motor development specialists. The validation results showed that the developed model obtained a feasibility score of 88% from academic experts, 92% from practitioner experts, & 96% from motor development experts, all categorized as “very feasible.” The small-group trial involving 16 participants achieved an average percentage of 91.75%, while the large-group trial involving 40 participants achieved 93.2%, both categorized as “very feasible.” The developed training model consists of six defensive formation patterns designed to improve defensive positioning, anticipation, communication, & team coordination in volleyball matches. The findings of the study indicate that the developed defensive formation training model is effective, practical, & feasible for use in volleyball training & physical education learning. The model provides innovative & engaging variations of defensive drills that can enhance player involvement & improve defensive performance in indoor volleyball games. Keywords: Defensive Training, Indoor Volleyball, Model Development.